Study of acoustoelasticity behavior of concrete material under uniaxial compression - Chaix, Jean-François; Lillamand, Ivan; Ploix, Marie-Aude; Garnier, Vincent; Corneloup, Gilles (The Journal of the Acoustical Society of America, 2008)
The general subject concerns the non destructive testing of prestressed structures in civil engineering. In this topic we are interested in the feasibility of stress evaluation in concrete by ultrasonic methods. To do that, we use the acoustoelasticity theory which exploits the nonlinear behaviour of media to establish the link between stress and ultrasonic velocity. This theory has been validated in homogeneous media and used in steel (to evaluated stresses in steel bolt for example). Concrete is a heterogeneous medium where the ultrasonic velocity measurement is more difficult than in steel. The scattered waves induce uncertainty in the measured values but the nonlinear behaviour of concrete is more important than the one of steel. We show an application in high performance concrete submitted to uniaxial compression. We measure velocities of longitudinal and transversal transmitted ultrasonic waves in the direction and perpendicularly to the stress at different level of the stress test. The sensibility of the different velocities is observed and the potential to evaluate stress in concrete is shown. Prospects particularly concern extension of tested formulations and in situ measurements. This study is supported by ANR-ACTENA, a French research program.